The Effects of Silibinin Combined With EGFR‐TKIs in the Treatment of NSCLC - Xiaocen Wang (Cancer Medicine)
ABSTRACT Background Currently, the most effective oral targeted therapies for NSCLC in clinical practice are EGFR‐TKIs. However, acquired drug resistance often leads to tumor progression and recurrence. EGFR overexpression and activation of its downstream pathways are primary contributors to both mutations in tumor cells and their development of drug resistance. Silibinin has been identified as a promising agent that can suppress EGFR signaling through multiple mechanisms. However, its poor water solubility and difficulty penetrating cell membranes result in rapid metabolism in vivo, and significantly affect its concentration in the blood. Methods We conducted a comprehensive search of the English PubMed database using various combinations of keywords, including “silibinin,” “epidermal growth factor receptor,” “phosphorylation,” “chemotherapy,” “nano,” and “non‐small cell lung cancer.” The results were then filtered for their relevance and impact on current treatment paradigms. Results This review presents a comprehensive exploration of the mechanisms underlying the EGFR autophosphorylation pathways that contribute to acquire drug resistance in. Additionally, this study delves into the potential of silibinin as a novel therapeutic agent for NSCLC, evaluating its advantages and limitations on the basis of existing research. The majority of the available data suggest that combining silibinin with first‐generation TKIs would yield promising outcomes because of additive or synergistic effects, suggesting that optimizing the time and dosage of each of these treatments is crucial for achieving the best results. Conclusion The existing evidence is inadequate to endorse the clinical application of nano silibinin for NSCLC treatment. Developing multifunctional nanomedicines that incorporate silibinin, EGFR‐TKIs, and other bioactive compounds is a recommended future strategy for NSCLC treatment.